Resilience of the urban tourist market in the face of the COVID-19 crisis. The case of Malaga - Benítez-Aurioles, Beatriz (Revista de Estudios Andaluces, 2022)
This article aims to verify the resilience of urban tourism in the face of the COVID-19 crisis, and identify its main features, taking the city of Malaga as a reference. The methodological approach provided by the economic analysis will be used to analyze the dynamics that have been registered in the accommodation market, both conventional (hotels) and short-term rental tourist housing. The data refer to demand, supply and price indicators for the period between September 2018 and the same month in 2021. The results of the analysis show clear signs of recovery in the tourism market as of spring 2021. More specifically, the role that residents of Spain acquire in the demand for hotel accommodation is confirmed. Likewise, in the peer-to-peer market, it is confirmed that, months after the lifting of mobility restrictions, the activity levels reached before the pandemic were exceeded. On this basis, it seems pertinent to reopen and rethink the debate on the carrying capacity of cities and the advisability of regulating the tourist accommodation market.